Collective syntheses of phenylethanoid glycosides by interrupted Pummerer reaction mediated glycosylations. Issue 9 (13th October 2018) - Zhao, Yueqi; Zeng, Jing; Liu, Yan; Xiao, Xiong; Sun, Guangfei; Sun, Jiuchang; Shu, Penghua; Fu, Dengxian; Meng, Lingkui; Wan, Qian
Abstract: The collective total syntheses of nine natural phenylethanoid glycosides (PhEGs) together with proposed Incanoside B in a divergent mode were described. By using a core disaccharide as common intermediate, our developed interrupted Pummerer reaction mediated (IPRm) glycosylations adopting latent-active strategy enables the efficient, concise and divergent syntheses of these bioactive PhEGs. Among them, five natural PhEGs, Darendoside B (1 ), Cistanoside G (3 ), Decaffeoyl acteoside (4 ), Kankanoside F (5 ) and 4′′′- epi -Leonoside F (7 ) were the first time being synthesized. According to the synthesis of 4′′′- epi -Leonoside F (7 ), we also elucidated the real structure of carbohydrate component of the PhEG isolated from Rehmannia glutinosa which was misled as "Leonoside F". GRAPHICAL ABSTRACT: